Pengaruh Pemijatan terhadap Kualitas Tidur Bayi Usia 3-4 Bulan di Posyandu Gelatik dan Nuri Kelurahan Tanjungunggat Wilayah Kerja Puskesmas Sei Jang Kota Tanjungpinang Tahun 2014 - Utami Dewi; Fidyah Aminin; Harvensica Gunnara (Journal of Ners and Midwifery, 2014)
Sleep is an essential need that must be met, especially in the development phase since brain and body development will occur during sleep. Thus, sleep disturbance is a problem that will cause adverse effects on growth and development, especially for babies. Sleep quality for babies can be improved by providing baby massage on a regular basis. The purpose of this study was to prove whether there were differences in sleep quality before and after the massage in babies aged 3-4 months in Gelatik and Nuri IHC (Integrated Health Center) of Tanjungunggat Village of Tanjungpinang Municipality. Design: This was a Quasi Experiment study with a pretest-posttest method. The sample consisted of 17 respondents selected by purposive sampling technique. The statistical test used in this study was a dependent t-test with a significance level of 0.05.Result: The results showed that there was no significant difference between baby sleep duration before and after the massage (p = 0.414). However, there was significant difference between the frequency of waking up before and after the massage (p = 0.001) and there was a significant difference between the duration of waking up before and after the massage (p = 0.046. Discuss: Based on the results of this study, it is suggested that mothers should improve their knowledge on the importance of baby massage provided by health professionals and the health professionals should provide and demonstrate clear, complete and sustained information to the mothers and other related parties surrounding the IHC.